Left ventricular systolic time intervals in patients with acute myocardial infarction. - Northover, B J (1980)
Left ventricular systolic time intervals were measured daily during 601 episodes of acute myocardial infarction. The ratio of pre-ejection period to ejection period during the first 24 hours permitted patients to be arranged in six prognostic groups with mortalities while in hospital ranging from 4 to 60 per cent. The only factors completely independent of the systolic time intervals which were shown statistically to be associated with high mortality while in hospital were defects in atrioventricular and intraventricular conduction.